ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR IURAN JAMINANA KESEHATAN NASIONAL (BPJS KESEHATAN) - Aisyah Fadila; Makhfiratun Nur Marbun, Abdillah Syaputra Siregar, Fitriani Pramita Gurning (Jurnal Kesehatan, 2023)
Background: Health Social Security Administering Body (BPJS Kesehatan) is a social health insurance service company appointed by the Government to provide health insurance coverage for JKN participants. Many participants do not routinely pay contributions every month, while participant compliance in paying contributions every month will be one of the factors that determines the sustainability of the JKN program. This condition still persists to this day. Research objective: The aim is to find out what factors influence compliance with paying contributions for national health insurance or BPJS Kesehatan. Research Methods: The method used in this research is descriptive quantitative. The research instrument was through a questionnaire and using simple random sampling. Results & Discussion As many as 67.5% of the public has understood the benefits of JKN itself. As many as 69.4%  of  the  public  stated  that  BPJS  contributions  were affordable and in accordance with the income of each person.